Twinning Lignosulfonate with a Conducting Polymer via Counter‐Ion Exchange for Large‐Scale Electrical Storage. (24th June 2019) - Che, Canyan; Vagin, Mikhail; Ail, Ujwala; Gueskine, Viktor; Phopase, Jaywant; Brooke, Robert; Gabrielsson, Roger; Jonsson, Magnus P.; Mak, Wing Cheung; Berggren, Magnus; Crispin, Xavier
Abstract: Lignosulfonate (LS) is a large‐scale surplus product of the forest and paper industries, and has primarily been utilized as a low‐cost plasticizer in making concrete for the construction industry. LS is an anionic redox‐active polyelectrolyte and is a promising candidate to boost the charge capacity of the positive electrode (positrode) in redox‐supercapacitors. Here, the physical‐chemical investigation of how this biopolymer incorporates into the conducting polymer PEDOT matrix, of the positrode, by means of counter‐ion exchange is reported. Upon successful incorporation, an optimal access to redox moieties is achieved, which provides a 63% increase of the resulting stored electrical charge by reversible redox interconversion. The effects of pH, ionic strength, and concentrations, of included components, on the polymer–polymer interactions are optimized to exploit the biopolymer‐associated redox currents. Further, the explored LS‐conducting polymer incorporation strategy, via aqueous synthesis, is evaluated in an up‐scaling effort toward large‐scale electrical energy storage technology. By using an up‐scaled production protocol, integration of the biopolymer within the conducting polymer matrix by counter‐ion exchange is confirmed and the PEDOT‐LS synthesized through optimized strategy reaches an improved charge capacity of 44.6 mAh g −1 . Abstract : The redox bio‐polyanion lignosulfonate (LS) can be integrated into the conducting polymer PEDOT:X by simple ion exchange. The adsorption mechanism is investigated by voltammetry and QCM‐D analysis. This synthetic route is efficient and fully scalable in aqueous medium thus enabling mass manufacturing of a new lignin composite PEDOT:LS as an electrode of green batteries.